캄보디아의 투자제도와 투자법제에 대한 고찰 - 조은래(Cho, Eun-Rae) (법학연구, 2017)
최근 외국의 투자자들은 캄보디아 투자에 주시하고 있다. 캄보디아는 일반 생산직 노동자들의 월 기본급이 이웃 베트남 및 태국과 비교하여 절반 또는 절반을 밑도는 수준으로 낮아 생산비용이 절감되며, 노동력 또한 우수한 공급지역이다. 캄보디아 정부는 외국의 기업들이 투자할 수 있도록 항상 문호를 개방하고 있으며, 일부 예외 업종을 제외하고 외자 100%에 의한 회사 설립이 가능하다. 또한 외국인의 토지 소유를 제외하고 외국 법인도 캄보디아 법인과 같은 대우를 받으며, 일정한 요건을 충족하는 경우에는 적격 투자프로젝트에 의해 법인세의 면제 또는 특별 상각의 적용, 관세의 면세, 수출세금의 면세, 기타 캄보디아 개발위원회의 원 스톱서비스 등의 혜택을 받는 인센티브가 있다. 캄보디아의 경제는 2016년 이후에도 지속적이고 안정적인 경제성장이 기대된다고 한다. 세계은행과 아세안 개발은행은 2016년 캄보디아의 경제성장률을 7.0% 정도로 예측하고 있으며, 세계은행은 2016년 7월 1일부로 캄보디아를 저소득국가에서 중저 소득국가로 격상하였다. 캄보디아 투자의 진출형태는 캄보디아 회사법에 의해 크게 유한책임회사, 외국법인의 주재원 사무소(법인대표 사무소), 외국법인의 지점 설치 등으로 분류할 수 있다. 2003년 3월에 개정 투자법이 제정되어 투자등록 제도를 보다 단순화함과 동시에 투명성과 예측가능성을 높여, 자의성을 배제하는 것을 목적으로 하고 있다. 2001년의 개정 토지법은 부동산의 소유권 관리양식을 확립하고 부동산 소유권 및 관련 권리서에 보증을 제공하는 것을 목적으로 하고 있으며, 또한 토지법은 2011년에 제정된 민법적용에 관한 법률에 의해 대폭 수정되었기 때문에 부동산에 관한 규제에 대해서는 민법 및 민사 법률의 규정을 확인하는 것이 중요하다. 캄보디아에서 외국인은 토지를 소유 할 수 없으며, 토지를 임차할 수는 있다. 또한 외국인의 공유건물전유부분 소유권취득에 관한 법률에 의해 다세대 주택의 구분소유 건물 단위의 소유가 인정된다. 캄보디아의 노동법은 원래 사회주의적 색채가 많았지만, 1997년의 헌법 개정으로 인하여 노동자와 노동조합의 권리를 존중하는 자유주의적인 경향으로 탈바꿈을 하였다. 고용, 해고, 임금, 근로시간, 휴가, 노동조합, 파업 등 노동자의 권리 및 노사관계 전반을 망라하고 있으며, 선진국의 노동법과 손색없는 내용이라고 할 수 있다. 한편 캄보디아 투자에 있어서 인건비 상승과 노사분규의 위험, 비싼 전기요금 및 물류비용, 불투명한 법률제도와 행정 절차의 부패 등의 과제들은 외국 투자자들이 주의해야 할 점들이다. 이에 캄보디아에 대한 외국인 투자를 위하여 투자환경 및 제도들을 살펴보고, 투자와 관련한 개정투자법과 부동산법, 노동법 등을 중심으로 살펴보고자 한다. Recently foreign investors are watching Cambodia. Cambodia has begun to solidify the remarkable progress it has achieved since adopting free-market economic policies in the 1990s. In Cambodia, wages of workers are generally lower than in neighboring countries and the labor force is also an excellent supply area. In addition, the Cambodian government has been improving their investment facilitation services. Foreign Direct Investments are treated in a non-discriminatory manner except for land-ownership, which is stated in the Constitution, and allowed to invest freely in many areas in Cambodia. Investment projects, which are approved by the Council for the Development of Cambodia(CDC) to grant investment incentives and guarantee, consist of Cambodian and foreign capital. Those projects were called “Investment Projects” under the Law on Investment of 1994 and are now called “Qualified Investment Projects (QIPs)” under the Law on Amendment to the Law on Investment of 2003. QIPs are entitled to the following investment incentives : QIPs may elect to receive a profit tax exemption or use special depreciation. Profit tax exemption : A tax holiday period is composed of “rigger period”+3 years+Priority Period. An annual Certificate of Obligation Satisfaction has to be obtained by the QIP to be entitled Profit Tax Exemption. A QIP shall be subject to a profit tax rate after its tax exemption period as determined in the Law on Taxation. And Special depreciation is 40% special depreciation allowance on the value of the new or used tangible properties used in the production or processing. The Law on Commercial Enterprise authorizes the formation of a limited company, either in a form of “private limited companies”or “public limited companies,” to carry on business in Cambodia. And Land Law was first promulgated in 1992 and was amended in August 2001. The 2001 Amendment to the Land Law especially aims to determine the regime of ownership for immovable properties in Cambodia for the purpose of guaranteeing the rights of ownership and other rights related to immovable properties. It also intends to establish a modern system of land registration that guarantees the rights of people to own land. It is prohibited for any foreigner to own land in Cambodia. Cambodian labor relations, employment and work terms and other labor-related matters are basically regulated by the Constitution and the 1997 Labor Law. The 2007 Labor Law, which was brought significant modification into the socialistic 1997 Labor Law, is quite liberal and protects the considerable rights of laborers and unions. A labor contract is subject to ordinary law and can be made in a form that is agreed upon by the contracting parties. When foreign investors invest in Cambodia, they should pay attention to rising cost of labor, labor disputes, expensive electric charges or logistics costs, uncertain legal systems and corruption of administrative procedures. KCI Citation Count: 2